Pisarenko V.G., Zavadiuk S.V. Study of impact energy of the material manufactured by metal injection molding. - Писаренко, В. Г.; Завадюк, С. В. (Problems of Tribology, 2018)
This paper covers the effect of sintering conditions, heat treatment and chemical composition on the impact energy of the sintering steel. It was shown the ways to improve impact energy of the sintered low alloy steel that was manufactured by metal injection molding without extra operations like Hot Isostatic Pressing. It was found that the chemical composition (specially such elements like Cr, Mn, Si) has the positive influence on the dynamic properties like impact energy. Also, it is important to decrease the porosity by increasing the sintering conditions such as temperature and holding time. There was investigated the influence of the heat treatment (hardness) on the impact energy of the sintered low alloy steel Catamold 8740, BASF. In order to improve impact energy, it is possible to apply hardening and high tempering for sintered steel. The impact energy, in this study, was measured according to Chappy test for notched and un-notched specimens. It has to be noticed a great variability of the results for un-notched specimens. Such effect can be explained by sensitivity of the porosity steel to the small defects, like non-homogeneity of the microstructure, open surface porosity, or residual thermal stresses. Furthermore, it was observed that the cracking surface for all test specimens after impact was flat without any plastic deformation.